2022
DOI: 10.3389/fcell.2022.826892
|View full text |Cite
|
Sign up to set email alerts
|

Stage Specific Transcriptomic Analysis and Database for Zebrafish Oogenesis

Abstract: Oogenesis produces functional eggs and is essential for fertility, embryonic development, and reproduction. The zebrafish ovary is an excellent model to study oogenesis in vertebrates, and recent studies have identified multiple regulators in oocyte development through forward genetic screens, as well as reverse genetics by CRISPR mutagenesis. However, many developmental steps in oogenesis, in zebrafish and other species, remain poorly understood, and their underlying mechanisms are unknown. Here, we take a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
6
2
Order By: Relevance
“…S2Y-DD). In situ hybridization had previously detected gja11 expression in follicle cells surrounding Stage II oocytes (cortical alveolus stage, 140–340 μm (Bogoch et al, 2022), which were not present in our samples), but not in Stage IB oocytes (Liu et al, 2022); our data detected gja11 expression at earlier stages presumably due to increased sensitivity. The oocyte partner of Gja11 could be encoded by gjc4a.1 ( cx44.2 ) or gjc4b ( cx43.4 ), which were expressed strongly and rather specifically in 30dpf oocytes (Santos et al, 2007) (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…S2Y-DD). In situ hybridization had previously detected gja11 expression in follicle cells surrounding Stage II oocytes (cortical alveolus stage, 140–340 μm (Bogoch et al, 2022), which were not present in our samples), but not in Stage IB oocytes (Liu et al, 2022); our data detected gja11 expression at earlier stages presumably due to increased sensitivity. The oocyte partner of Gja11 could be encoded by gjc4a.1 ( cx44.2 ) or gjc4b ( cx43.4 ), which were expressed strongly and rather specifically in 30dpf oocytes (Santos et al, 2007) (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 47%
“…Oocyte stages recovered are limited by the scRNA-seq protocol, which passes cells through a 40µm filter. According to recent staging criteria (Bogoch et al, 2022), we would recover only oocytes from the earliest two stages, the symmetry-breaking stage (8–20 μm Selman Stage IA, oogonia and meiotic oocytes from leptotene to pachytene), and early Selman Stage IB, nuclear cleft, 15–50μm, oocytes from pachytene to mid-diplotene (Selman et al, 1993, Bogoch et al, 2022)). Comparison of gene expression patterns with other transcriptomic analyses of zebrafish oocytes (Wong et al, 2018, Zhu et al, 2018, Can et al, 2020, Bogoch et al, 2022) are difficult because at least some of the oocyte sizes we examined were not analyzed or were mixed with larger oocytes, and in other studies, oocyte sizes were listed only in relative terms, so comparison wasn’t possible (Cabrera-Quio et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To culture oocytes, we isolated them form adult ovaries, where they are abundant (Fig. 2A), using our isolation protocol 8,50 , as also described above (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we wanted to biochemically determine the solubility state of Buc granules and test whether they constitutes a separate non-soluble phase in physiological conditions. We previously developed a method for a size-based isolation of stage specific oocytes from ovaries 8 , which is successfully used for biochemical and omics analyses 44,50 . We first used this method to isolate oocytes at sizes of 50-100 μm in diameter, which represent mature Bb stages, from Buc-GFP transgenic ovaries and confirmed that all oocytes showed a clear signal of Buc-GFP in the mature Bb (Fig.…”
Section: Live Imaging Molecular and Biochemical Evidence For Buc Depe...mentioning
confidence: 99%
See 1 more Smart Citation